2019
DOI: 10.1039/c9gc01372e
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of chitosan with lignin to produce active materials by waste valorization

Abstract: Active films are produced by a grafting reaction based on the reactivity between chitosan amino groups and lignin hydroxyl groups. This opens a new route for the valorization of lignin, with the possibility of tuning the anti-oxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Among the available biomass precursors, polysaccharides stand out as the most promising and have already dominated research revolving around the design of new biobased nanocomposites. Among those of interest, chitosan-based marine fishery waste stands as the sole cationic polysaccharides, its amino groups being the basis of its catalytic activity, metal-chelating ability, and biological efficiency. Moreover, chitosan is biocompatible, fully degradable, and readily soluble in acidic aqueous media and can be used in several forms, including a colloidal state, in coagulated forms as hydrogels or microspheres. It is also moldable and can be caste on demand at a desirable thickness as nanostructured films. The excellent film-forming ability of chitosan has opened great opportunities for biobased packaging materials. Coupled to the possibility of conjugating chemicals through its primary amine, a subtly controlled release of active ingredients from chitosan films has also been recently demonstrated. The poor mechanical strength of chitosan has also been overcome by addition of a small amount of nanosized fillers, for example, Montmorillonite, graphene oxide, hydroxyapatite, carbon nanotubes, , and metal oxide nanoparticles, among others. , Recently, nanofibrils, nanocrystals, and nanowhiskers of cellulose, chitin, lignin, and other biomass-sourced building blocks have also been used for sustaining chitosan films. …”
Section: Introductionmentioning
confidence: 99%
“…Among the available biomass precursors, polysaccharides stand out as the most promising and have already dominated research revolving around the design of new biobased nanocomposites. Among those of interest, chitosan-based marine fishery waste stands as the sole cationic polysaccharides, its amino groups being the basis of its catalytic activity, metal-chelating ability, and biological efficiency. Moreover, chitosan is biocompatible, fully degradable, and readily soluble in acidic aqueous media and can be used in several forms, including a colloidal state, in coagulated forms as hydrogels or microspheres. It is also moldable and can be caste on demand at a desirable thickness as nanostructured films. The excellent film-forming ability of chitosan has opened great opportunities for biobased packaging materials. Coupled to the possibility of conjugating chemicals through its primary amine, a subtly controlled release of active ingredients from chitosan films has also been recently demonstrated. The poor mechanical strength of chitosan has also been overcome by addition of a small amount of nanosized fillers, for example, Montmorillonite, graphene oxide, hydroxyapatite, carbon nanotubes, , and metal oxide nanoparticles, among others. , Recently, nanofibrils, nanocrystals, and nanowhiskers of cellulose, chitin, lignin, and other biomass-sourced building blocks have also been used for sustaining chitosan films. …”
Section: Introductionmentioning
confidence: 99%
“…Sinapic acid has the highest radical activity due to di-ortho-methoxyl substitution, ferulic acid has an intermediate activity, and coumaric acid has no antioxidant activity. The results could confirm that the higher concentration of syringyl, the higher the antioxidant activity (Crouvisier-Urion et al 2019). Biopolymer matrix from Poly(lactide) (PLA)-lignin results in a good dispersion.…”
Section: Active Packagingmentioning
confidence: 70%
“…The UV–vis absorption spectra of DAL, DAL-12ane, and DAL-11ene are shown in Figure b. The absorption peak of DAL at 218 nm was related to the unsaturated CC or CO bonds, while that at 280 nm corresponded to the phenolic hydroxyl and aromatic moieties of the DAL . The spectra of DAL-12ane and DAL-11ene both showed a small blue shift (213 nm) compared to that of DAL, which indicated that the aggregation extent of aromatic moieties decreased due to the introduction of long flexible chains.…”
Section: Results and Discussionmentioning
confidence: 90%
“…The absorption peak of DAL at 218 nm was related to the unsaturated CC or CO bonds, while that at 280 nm corresponded to the phenolic hydroxyl and aromatic moieties of the DAL. 40 The spectra of DAL-12ane and DAL-11ene both showed a small blue shift (213 nm) compared to that of DAL, which indicated that the aggregation extent of aromatic moieties decreased due to the introduction of long flexible chains. In addition, the peak at 280 nm declined obviously for DAL-12ane and DAL-11ene due to the consumption of phenolic hydroxyl groups by the esterification reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%